2015
DOI: 10.1007/s10646-015-1570-1
|View full text |Cite
|
Sign up to set email alerts
|

An environmental forensic approach for tropical estuaries based on metal bioaccumulation in tissues of Callinectes danae

Abstract: The blue crab Callinectes danae is distributed throughout the Atlantic coast and this study aimed to evaluate a environmental forensics approach that could be applied at tropical estuarine systems where this species is distributed, based on the metal concentrations in its tissues. For this purpose, blue crab samples were collected in 9 sites (distributed in 3 areas) along the Santos Estuarine System, state of São Paulo, Brazil. The concentrations of Al, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb and Zn were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 36 publications
0
5
0
3
Order By: Relevance
“…According to Rainbow (1988) and Bordon et al (2016), metals absorbed by gills and/or the epidermis can only be proportionally transferred to muscle tissue if in excess, depending on the pattern of accumulation of each species and chemical properties of the considered element. Thus, metals absorbed by gills should not be directly and proportionally transferred to muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Rainbow (1988) and Bordon et al (2016), metals absorbed by gills and/or the epidermis can only be proportionally transferred to muscle tissue if in excess, depending on the pattern of accumulation of each species and chemical properties of the considered element. Thus, metals absorbed by gills should not be directly and proportionally transferred to muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have assessed metal concentrations in C. danae tissues for biomonitoring purposes (Virga et al, 2007;Virga and Geraldo, 2008;Bordon et al, 2016); some have reported that different metals may present different target tissues and bioaccumulate differently in distinct tissues (Bordon et al 2012b;Lavradas et al, 2014). The combination of the uptake and depuration processes of each tissue and in the whole organism would lead to the following processes: metals can be efficiently excreted, can accumulate in immobilized form, or can remain active in the tissue and lead to deleterious effects in the animals (Rainbow, 1988(Rainbow, , 1998(Rainbow, , 2007(Rainbow, , 2002.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are benthic organisms that live in close contact with potentially contaminated sediments and are, therefore, considered important contamination bioindicators [4,6,14]. Studies around the world that evaluate the concentration of mercury in swimming crabs that inhabit estuaries indicate average values between 0.035 mg kg −1 and 0.496 mg kg −1 [5,6,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Callinectes danae é uma das várias espécies de caranguejos recomendadas como biomonitor ambiental, capaz de fornecer respostas biológicas em áreas contaminadas (Bordon et al 2012(Bordon et al , 2015. A sobrevivência desses invertebrados depende da qualidade ambiental do estuário, sendo assim, as concentrações de metais nos tecidos dos siris-azuis devem ser monitoradas, já que esta espécie é um recurso pesqueiro importante nas comunidades locais (Severino-Rodrigues et al 2001).…”
Section: O Siri Callinectes Danaeunclassified